The Urgency of Banks in Implementing the Precautionary Principle as Consumer Protection in the Standard Clauses of Credit Agreements - Farid Irfan Siddik; Astutik, Sri; Widodo, Ernu; Soekorini, Noenik; Abidin, Izzah Khalif Raihan (Universitas Airlangga, 2024)
The importance of the bank in applying the precautionary principle contributes to ensuring a sound banking system and protecting the country’s economy. In lending, the precautionary principle was manifested in a standard agreement between the bank as the creditor and the customer as the debtor. Credit agreements can lead to disputes, where the debtor sues the bank for violating the principle of consumer protection because it applies standard clauses in the credit agreement. The research method used is legal research with a statute approach and a conceptual approach). The results state that the application of the precautionary principle in making standard agreements manifests itself in the prohibition of financial service business actors including exoneration clauses to the detriment of financial service consumers as stipulated in Article 18 paragraph (1) of the Consumer Protection Act and OJK Regulation No. 6/POJK.07/Tahun 2022 concerning Consumer and Community Protection in the Financial Services Sector.